Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Suppose that $*$ is an associative and commutative binary operation on a set $S$. Let $H=\{a\in S\mid a*a=a\}$. Show that $H$ is closed under $*$.

I started this problem by listing the definitions of * being commutative and associate. So I let $a,b\in H$. I now need to show that $a*b$ is in $H$. So I said $a*b=(a*a)*(b*b)$ because of what it means to be a member of $H$. I'm not sure where to go from there or how to prove it is associative. Any help?

share|improve this question
    
You want to prove that $(ab)(ab)=ab$. This is because $H$ consists of the objects $x$ that satisfy the equation $x^2=x$. You want to show that if $a$ and $b$ satisfy that equation, so does $ab$. First use associativity. –  André Nicolas Feb 7 '12 at 17:59
    
as you stated you should prove that a*b in H if a and b in H. a*b in H means that (a*b)*(a*b)=(a*b). can you prove this? –  miracle173 Feb 7 '12 at 18:02

1 Answer 1

up vote 4 down vote accepted

You don't need to prove $*$ is associative; you already know it is.

The only thing you need to show is that if $a$ is in $H$ and $b$ is in $H$, then $a*b$ is in $H$.

When is an object $x$ in $H$? $x$ is in $H$ if and only if $x$ is in $S$, and $x*x=x$.

So in order to show that $a*b$ is in $H$, you need to show that:

  • $a*b$ is in $S$; and
  • $(a*b)*(a*b) = a*b$.

Why is $a*b\in S$? Because $a\in S$, $b\in S$, and $*$ is a binary operation in $S$. Remember that a binary operation is a function of type $*:S\times S \to S$, so $a*b$ maps to some element of $S$.

Why is $(a*b)*(a*b)=(a*b)$? Well, we know $a\in H$, so we know $a*a = a$; we know $b\in H$, so we know $b*b=b$. Now use the fact that $*$ is associative and commutative to show that $(a*b)*(a*b)=a*b$, and this will show that if $a\in H$ and $b\in H$, then $a*b\in H$. That is what you need to show in order to show that $H$ is closed under $*$.

share|improve this answer
1  
Okay, how does this look: (a∗b) = a∗(b∗b) = (a∗b)∗b = (b∗a)∗b = [b∗(a∗a)]∗b = b∗[(a∗a)∗b] = b∗[a∗(a∗b)] = (b∗a)∗(a∗b) = (a∗b)∗(a∗b) –  user23793 Feb 7 '12 at 18:12
    
@user23793: Fine, though it seems like it would be simpler to do $(a*b)*(a*b) = (a*b)*(b*a) = a*((b*b)*a) = a*(b*a) = a*(a*b) = (a*a)*b = a*b$ –  Arturo Magidin Feb 7 '12 at 18:16

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.